Дiячi украïнськоï культури щодо дискусïï орiенталicтiв та окциденталicтiв у Греко-католицькiй Церквi (1920-1930 рр.) - Kramar, Rotysław (Acta Polono-Ruthenica, 2008)
The theme of this article is the discussion about Greek Catholic Church tendency of the development in Galician uniate priests’ surrounding such as orientalism and oxydentalism. Spiritual debates were about the ritual forms in epoch of the new challenge of the modernizing world; which of them would be more suitable for the Church. They transformed to the wide discussion about the civilizing development of the Ukraine by means of the scientists and cultural activists.